2015
DOI: 10.1002/zaac.201400582
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) and Cadmium(II) Complexes of 5‐Ferrocenyl‐1H‐tetrazole: Synthesis, Structures, and Catalytic Effects on Thermal Decomposition of Energetic Compounds

Abstract: Abstract. Alkyl-substituted ferrocenes as ferrocene-based burning rate (BR) catalysts in composite solid propellants have high migration tendency and strong volatility during processing and long-time storage of the propellants. For developing low-migratory alternatives, zinc(II) and cadmium(II) complexes, [Zn(phen) , and [Cd(bpy) 2 (FcTz) 2 ]·H 2 O (4) (bpy = 2,2Ј-bipyridine; phen = 1,10-phenanthroline; FcTz = 5-ferrocenyl-1H-tetrazolate), derived from 5-ferrocenyl-1H-tetrazole (HFcTz) were synthesized and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Given the positive catalytic effects of Cu II and Cd II ions, , EMOFs constructed with these ions as metal centers are expected to have a great impact on the thermal decomposition of AP. We synthesized two 3D coordination compounds based on Cu II and Cd II cations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the positive catalytic effects of Cu II and Cd II ions, , EMOFs constructed with these ions as metal centers are expected to have a great impact on the thermal decomposition of AP. We synthesized two 3D coordination compounds based on Cu II and Cd II cations.…”
Section: Introductionmentioning
confidence: 99%
“…Energetic coordination compounds used as the catalysts/additives to the propellants have attracted tremendous interests for such compounds not only contain more N=N or C=N groups, which hold a higher positive enthalpy formation but also provide fresh metal or metal oxide at the molecule level on the propellant surface, which could improve combustion performance when the compounds are used as the catalysts/additives to the propellants . Hence, a lot of energetic metal compounds have been researched recently as catalysts for the thermal decomposition of AP, RDX, and HMX, such as a series of ferrocenyl compounds, two energetic complexes, Co(TO) 2 (DNBA) 2 (H 2 O) 2 and Cu(TZA)(DNBA), incorporating 3,5‐dinitrobenzoic acid and azole ligands, [Mn(BTO)(H 2 O) 2 ] n [BTO = 1H,1′H‐[5,5′‐bitetrazole]‐1,1′‐bis(olate)] . Among those energetic metal compounds, most of them show excellent catalytic activities for AP and RDX thermal decomposition, however, rare have distinct catalytic effects on the thermal decomposition of HMX [the oxidizer in nitrate ester plasticized polyether (NEPE) solid propellant].…”
Section: Introductionmentioning
confidence: 99%
“…We have synthesized a few metal compounds derived from HFcTz and found that they show high effects on the thermal decomposition of some energetic compounds. [10d], In terms of the easy deprotonation nature of HFcTz a number of guanidine and imidazole salts with 5‐ferrocenyl‐1H‐tetrazolate as anion were synthesized and the catalytic activity evaluation results showed that some salts exhibit higher activity than that of Catocene in the acceleration of the thermal decomposition of AP. [11e] According to the catalytic mechanisms of AP‐based solid propellants, the added ferrocene‐based BCRs decomposes and iron atoms in the BCRs react with oxygen to form Fe 2 O 3 nanoparticles, which are the true catalyst and display excellent catalytic activity in the thermal disintegration of AP…”
Section: Introductionmentioning
confidence: 99%